Availability and price changes of potential medicines and equipment for the prevention and treatment of COVID-19 among pharmacy and drug stores in Bangladesh; findings and implications (Bangladesh Journal of Medical Science, 2020)
Objective: There are concerns with increased prices and drug shortages for pertinent medicines and personal protective equipment (PPE) to prevent and treat COVID-19 enhanced by misinformation. Community pharmacists and drug stores play a significant role in disease management in Bangladesh due to high co-payments. Consequently, a need to review prices and availability in the pandemic.Materials and Methods: Multiple approach involving a review and questionnaire among pharmacies and stores early March to end May 2020.Results and Discussion: 170 pharmacies and drug stores took part, giving a response rate of 63.9%. Encouragingly, no change in utilization of antimalarial medicines in 51.2% of stores despite global endorsements. However, increased utilisation of antibiotics (70.6%), analgesics (97.6%), vitamins (90.6%) and PPE (over 95%). Encouragingly, increases in purchasing of PPE. No increase in prices among 50% of the stores for antimalarials, with a similar situation for antibiotics (65.3%), analgesics (54.7%), and vitamins (51.8%). However, price increases typically for PPE (over 90% of stores). Shortages also seen for medicines and PPE, again greater for PPE.Conclusions: The pandemic has impacted on the supply and prices of medicines and PPE in Bangladesh. Key stakeholder groups can play a role addressing misinformation, with enhanced local production helping address future shortages and prices.Bangladesh Journal of Medical Science Vol.19(0) 2020 p. S 36-S 50